Objective memory as an indicator of functional impairment in native Spanish-speaking patients with HIV infection - García-Torres, Amalia; González-Andrade, Alejandro; Fernández-Muñóz, Juan José; Pérez-García, Miguel; Vergara-Moragues, Esperanza (AIDS Care - Psychological and Socio-Medical Aspects of AIDS/HIV, 2020)
Objective memory is one of the most affected cognitive areas in patients with HIV and perhaps one of the best predictors of daily functioning problems. Its relationship with biological markers, mood symptoms, and cognitive complaint is unclear and has received little attention in native Spanish-speakers. The goal of this study is to explore the relationships between the above-mentioned variables and their prediction of objective memory performance in native Spanish-speakers. HIV-related biological markers, mood symptoms, cognitive complaint, and objective memory were assessed in a sample native Spanish-speaking HIV patient with possible cognitive impairment. The results revealed deficit in short- and long-term memory while recognition was retained. Hierarchical regression analysis showed that the combination of independent variables significantly predicted performance in recognition, indicating that the pattern of impairment in short- and long-term memory is related to a difficulty to learn new information discriminately. The non-prediction of short- and long-term memory performance may be related to the inability to estimate the deficit in objective memory. These results show the need to perform specific interventions in mnesic processes, in view of the relation between this cognitive process and patients’ daily functioning.
Keywords: memory disorders; HIV; mood disorders; biological markers; cognition disorders; Scopus; JCR